Evaluation of Integrated Pest Management Practices against the Incidence of White Fly and Bean Yellow Mosaic Virus (BYMV) in Rajmash (Phaseolus vulgaris L.) - Seetharamu, P.; Sekhar, D.; Rameshnaik, N.; Jogarao, P.; Sanddepnaik, B. N.; Srinivasarao, M.; Ramarao, G.; Sureshkumar, M. (International Journal of Bio-resource and Stress Management, 2024)
The present field experiment was carried out at Regional Agricultural Research Station farm, Chintapalle, Andhra Pradesh, India in three consequent years during Rabi seasons (October-February) of 2020–21, 2021–22 and 2022–23 to evaluate the Integrated Pest Management practices to contain insect pests on rajmash (Phaseolus vulgaris L.). The experiment was carried out using ten treatments viz., seed treatment with imidacloprid @ 6 ml kg-1 seed, seed treatment intercrop with mustard (6:1), seed treatment intercrop with maize (6:1), seed treatment border crop 2 rows with maize, seed treatment yellow sticky traps @ 25 ha-1, seed treatment+NSKE @ 5%, seed treatment +neem oil @ 5 ml l-1, seed treatment dimethoate @ 2 ml l-1, seed treatment acetamiprid @ 0. 2 g l-1 and untreated control (without seed treatment) replicated thrice. The pooled data revealed that all the treatments were significantly superior over check. Among the treatments, seed treatment with imidacloprid @ 6 ml kg-1 seed+foliar spray with acetamiprid @ 0.2 g l-1) was proved effective in recording lowest mean whitefly population (5.66) with 65.06 mean per cent reduction of the whitefly population over untreated control and also resulted lowest mean incidence of bean yellow mosaic disease (5.54%) at 45 DAS. The highest net profit (Rs. 6840 ha-1) was obtained from the plots treated with acetamiprid followed by dimethoate. The next best treatments were rajmash+maize intercropping (6:1) and neem oil registered with the net profit of `Rs. 5730, ` 5200 and `Rs. 2275 ha-1, respectively.